How persistent identifiers can save scientists time. Issue 15 (19th June 2018) - Meadows, Alice; Haak, Laure
Abstract: Research information is useful only if it can be shared—with other researchers, with research organizations (institutions, laboratories, funders and others), and with the wider community. In our digital age, that means sharing information between data systems. Persistent identifiers (PIDs) provide unique keys for people, places and things, which enables accurate mapping of information between these systems and supports the research process by facilitating search, discovery, recognition and collaboration. This article reviews the main PIDs used in research—digital object identifiers for publications, ORCID iDs for researchers, and a proposed new identifier for research organizations—as well as demonstrating how they are being used, and how, in combination, they can increase trust in research and the research infrastructure. Abstract : Persistent identifiers enable trusted connections between researchers, their publications and their organizations that ultimately build trust in research, reducing the potential for errors and saving researchers time and hassle.